Determination of antimicrobial resistance gene variations using Tet and Str genes in freshwater fish species - Dogan, Sibel; Onalan, Sukru (C M B Assoc, 2023)
With the rapid development of aquaculture, antibiotics are widely used for prophylactic and therapeutic purposes to reduce economic losses caused by disease outbreaks. Considering that most antibiotics applied to humans and animals are partially metabolized and not eliminated, it is evident that these antibiotic residues can have negative effects on natural aquatic organisms after reaching the receiving environment, such as rivers and reservoirs. Therefore, it is believed that this indiscriminate use of antibiotics is now beginning to affect aquatic organisms in natural environments, outside of closed environments. In this study, tissue samples were taken from seven fish species in the Firat River. Specific primer sets were designed for Tet and Str genes, which are known to play a role in antibiotic resistance mechanisms. The changes in gene expression levels were then examined. The results showed that the expression levels of Tet and Str genes associated with antibiotic resistance were more than two-fold higher in Cyprinus carpio and Chondrostoma regium species compared to a control group that did not use antibiotics. A moderate expression level was observed in Capoeta trutta, Acanthobrama marmid, Capoeta umbla, and Barbus grypus species. In addition, in Luciobarbus mystaceus species, the Tet gene was expressed at a meaningless level, while the Str gene was downregulated. Therefore, it is believed that this species may not have encountered or has previously encountered antibiotics at low levels, leading to the control levels of the resistance mechanism.
Keywords: Firat river; antimicrobial resistance; Tet; Str; gene expression